Enhancing mechanical properties of polylactic acid through the incorporation of cellulose nanocrystals for engineering plastic applications - Shih-Chen Shi; Chia-Feng Hsieh; Dieter Rahmadiawan (Teknomekanik, 2024)
This study investigates the potential of enhancing the mechanical properties of polylactic acid (PLA) using cellulose nanocrystals (CNC). Recognized for their high specific strength and stiffness, CNCs are considered to improve the performance of PLA in engineering plastic applications. The synthesis involves a twin-screw extrusion process, which facilitates the uniform dispersion of CNC within the PLA matrix. The mechanical properties, including tensile strength and elongation at break, are comprehensively analyzed, highlighting the effects of CNC concentrations on the performance of PLA composites. Notably, the addition of 1 wt% CNC resulted in a 20% increase in strain at break compared to pure PLA, demonstrating enhanced ductility. Additionally, the thermal resistance of the composite increased by 0.3% with the inclusion of 5 wt% CNC. This study highlights the positive effect of CNC addition on the mechanical properties of PLA composites, making them more suitable for specialized engineering uses.